Legal Protection For Consumers In Online Buying and Selling Transactions: A Civil Law Perspective - Ilfa Luthfia Hidayah; Dea Fadilla Tinura; Lisa Chusnul Khotimah; Deni Yusup Permana; Diky Dikrurahman (Journal Of Social Science (JoSS), 2025)
The rapid development of information and communication technology has had a significant impact on the pattern of buying and selling transactions, one of which is through online platforms. Although this transaction offers convenience and convenience for consumers, there are also challenges related to the protection of consumer rights. This article discusses legal protection for consumers in online buying and selling transactions from a civil law perspective. The main focus of this discussion is on consumer rights regulated in the Consumer Protection Law as well as the protection of consumers in transactions that occur in the digital space. This discussion covers various issues, such as the responsibility of business actors, quality assurance of goods or services, the right to get clear and correct information, and effective dispute resolution mechanisms. In the context of civil law, this article examines how legal protection for consumers can be applied to provide legal certainty and prevent adverse practices that can put consumers at a disadvantage. It is hoped that this article can provide insight into the importance of comprehensive regulations in protecting consumer rights in online buying and selling transactions.